Entropy generation in a chemical reaction - Miranda, Enrique Nestor (2010)
Entropy generation   in a chemical reaction is analyzed without using the general formalism of non-equilibrium thermodynamics at a level adequate for advance undergraduates. In a first approach to the problem, the phenomenological kinetic equation of an elementary first order reaction is used to show that  entropy production is always positive.  A second approach assumes that the reaction is near equilibrium to prove that the entropy generated is always greater than zero, and no reference is made to the kinetics of the reaction. Finally, it is shown that entropy generation is related with fluctuations in the number of particles in equilibrium, i.e. it is associated to a microscopic process.